2007
DOI: 10.1111/j.1439-0531.2006.00786.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Fertility with Numbers of Antral Follicles within a Follicular Wave During the Oestrous Cycle in Beef Cattle

Abstract: The association between conception rate at first service and numbers of follicles developed during a follicular wave was examined in 102 suckled beef cows and 14 heifers. Follicular development was monitored using ultrasonography for either two (trial 1) or three (trial 2) consecutive oestrous cycles (pre-breeding, breeding and post-breeding equivalent). Animals were examined on alternate days from day 6 after first oestrus (day 0) until ovulation and from day 6 after insemination until next ovulation or day 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
6
1
2
Order By: Relevance
“…Positive partial correlations were also found between ovarian size and prebreeding BW, weight:height ratio, or ADG; thus, the association between AFC and body size and growth performance may be the consequence of a treatment or genetic effect on body size, with AFC being increased because of positive relationships between ovarian size and body size and between ovarian size and AFC. In contrast with recently reported decreased fertility in beef ) and dairy (Mossa et al, 2012) cows and heifers with low (≤15 follicles) vs. high (≥25 follicles) AFC, pregnancy rate did not differ between low-and high-AFC beef heifers in the present study or in a study reported by Starbuck-Clemmer et al (2007). Cushman et al (2009) reported that AFC increases with age, reaching a maximum at about 5 yr and declining thereafter.…”
Section: Discussioncontrasting
confidence: 55%
“…Positive partial correlations were also found between ovarian size and prebreeding BW, weight:height ratio, or ADG; thus, the association between AFC and body size and growth performance may be the consequence of a treatment or genetic effect on body size, with AFC being increased because of positive relationships between ovarian size and body size and between ovarian size and AFC. In contrast with recently reported decreased fertility in beef ) and dairy (Mossa et al, 2012) cows and heifers with low (≤15 follicles) vs. high (≥25 follicles) AFC, pregnancy rate did not differ between low-and high-AFC beef heifers in the present study or in a study reported by Starbuck-Clemmer et al (2007). Cushman et al (2009) reported that AFC increases with age, reaching a maximum at about 5 yr and declining thereafter.…”
Section: Discussioncontrasting
confidence: 55%
“…A novel finding in this study was that heifers that calved in the first 21 d of their first calving season had greater numbers of antral follicles detectable by ultrasonography at 14 months of age. Antral follicle count has been reported as an indicator of fertility in heifers and cows in a numbers of studies (Cushman et al, 2009;Mossa et al, 2012;Tessaro et al, 2011); however, there have also been studies where antral follicle count did not reflect fertility in cattle (Snelling et al, 2012;Starbuck-Clemmer et al, 2007). Mossa et al (2012) reported a tendency for dairy cows with low follicle numbers to have an increased number of services per conception and lower pregnancy rates in a seasonal production system.…”
Section: Traitmentioning
confidence: 99%
“…Contraditoriamente, STARBUCK-CLEMMER et al (2007), trabalhando com fêmeas taurinas de corte, demonstraram que a categoria animal influenciou na quantidade de folículos ≥4mm de diâmetro presentes nos ovários, verificando uma menor CFA nas vacas paridas em relação as novilhas. Os autores justificaram estes achados pela idade das vacas utilizadas na pesquisa, entretanto, no presente estudo, a maioria dos animais apresentava idades inferiores a 10 anos (BURNS et al, 2005).…”
Section: Resultsunclassified
“…A partir do procedimento de regressão logística, também não observou-se aumento na probabilidade de concepção com o acréscimo no número de folículos (P>0,27). De forma similar, STARBUCK-CLEMMER et al (2007) também não demonstram variação entre a taxa de concepção e a quantidade de folículos antrais em fêmeas taurinas Tabela 1 -Comparação da contagem de folículos antrais (CFA) em fêmeas Nelores de diferentes grupos de categorias animais, dias pós-parto, diâmetro ovariano, presença de corpo lúteo eescore de condição corporal (ECC),submetidas a um protocolo de inseminação artificial em tempo fixo (IATF).…”
Section: Resultsunclassified